Navigating older adults care: insights from caregivers and community health workers in Ngestiharjo, Bantul, Yogyakarta - Hafidz, Firdaus; Monanda, Adelia Pramudita; Fitriani, Dewi Caesaria; Hariyanti, Tatik; Jamiah , Erni (Universitas Gadjah Mada, 2024)
Purpose: This study aimed to elucidate the knowledge, attitudes, and practices of older adult caregivers in Ngestiharjo, Bantul, Yogyakarta, Indonesia, towards older adult care and to discern the role of Community Health Workers (CHWs). Methods: A mixed-methods approach was employed between April and June 2023, encompassing quantitative data collection with a cross-sectional approach from 253 older adult caregivers via a pretested questionnaire and qualitative insights with a descriptive approach from focus group discussions with seven CHWs. The data were analyzed using descriptive analysis and thematic analysis. Results: The caregivers were predominantly female (67.2%) and over the age of 50 (46.6%), with the most common occupation being housekeeping (34.8%). Knowledge deficits were noted in several areas, with mean scores of 0.53 for depression signs, 0.56 for physical exercise, 0.73 for sleep quality, and 0.79 for fall risk. Caregivers' sleep quality and fall risk knowledge were better than depression and physical exercise. Attitude scores averaged 82.42 ± 20.42 (out of 125), showing moderate confidence in caregiving activities. Practices related to older adult care showed promising results, especially in maintaining a clean living environment (mean Score: 4.08 ± 0.86). The pivotal role of CHWs in bridging this knowledge gap and facilitating healthcare access was underscored. Conclusion: The study highlights the need for targeted educational programs to improve the knowledge and practices of caregivers, particularly in physical exercise and mental health areas. Strengthening the role of CHWs is essential to enhancing caregiving outcomes.